Penerapan Teknik Mind Maps dalam Meningkatkan Keterampilan Menulis - ., Yusrumaida (Universitas Pendidikan Ganesha, 2018)
This study aims at improving students’ writing competency in class VIII SMP Negeri 2 Singaraja through the use of mind mapping technique. It is a classroom action research with two cycles, involving planning, implementation, observation or evaluation, and reflection. The subject of this study was 37 students involving 14 boys and 23 girls in class VIII SMP Negeri 2 Singaraja. The data were analyzed by using statistic descriptive analysis. The result of the analysis showed that the mean score of students’ writing competency in cycle I was 65 and the mean score in cycle II was 80. It indicated that the writing competency achievement from cycle I to cycle II improved 15 points. Based on the data analysis and the discussion, it can be concluded that students’ writing competency improves through the use of mind mapping technique in class VIII-5 SMP Negeri 2 Singaraja. It is also suggested for the English teachers to implement mind mapping technique to improve students’ writing competency.